1988
DOI: 10.1080/10862968809547629
|View full text |Cite
|
Sign up to set email alerts
|

Young Children's Written Language Knowledge: What Environmental and Functional Print Reading Reveals

Abstract: The purpose of this study was to describe attempts by nonword readers, novice word readers, and expert word readers to read environmental and functional print items. Eighty-one children aged 3 to 6 years were included in the study. Children were assessed for word-reading ability and letter-naming knowledge. They were then categorized into reader groups based on ability to read preprimer and primer words in isolation. Next, children were shown nine print items and asked, "What can you read here?" Responses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0
1

Year Published

1989
1989
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 7 publications
5
31
0
1
Order By: Relevance
“…, Mason (1980), and Masonheimer, Drum, and Ehri (1984) found that the transfer of words learned in the context of environmental print to traditional word reading was very poor. McGee, Lomax, and Head (1988) found similar results to these previous studies with one minor exception; nonreaders did devote limited attention to graphic detail. Johns (1980) found that children who were low achievers in reading at the conclusion of first grade evidenced poorly developed concepts about printed language.…”
supporting
confidence: 80%
“…, Mason (1980), and Masonheimer, Drum, and Ehri (1984) found that the transfer of words learned in the context of environmental print to traditional word reading was very poor. McGee, Lomax, and Head (1988) found similar results to these previous studies with one minor exception; nonreaders did devote limited attention to graphic detail. Johns (1980) found that children who were low achievers in reading at the conclusion of first grade evidenced poorly developed concepts about printed language.…”
supporting
confidence: 80%
“…The results of this research agreed with that of earlier work (McGee, Lomax, & Head, 1988) which stated that children, even if they are not able to read the environmental print conventionally, observe and comment on specific letters. The fact that Greek preschoolers seem able to discern successfully between the two alpabetical systems which proliferate in their literary environment, gives strong evidence to assume that environmental print contributes to their literary development.…”
Section: Discussionsupporting
confidence: 82%
“…a Ruffles potato chip bag) than functional print items (e.g. McGee, Lomax & Head, 1988). In addition, although preschoolers tend to identify the labels as either categories (toothpaste) or functions (to clean teeth) (Goodman & Altwerger, 1981;Morgan, 1987), they gradually move from gross approximations about print to conventional reading looking for individual words and letters.…”
Section: Environmental Printmentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies have suggested that the main contribution of letter knowledge to early literacy is to improve visual word recognition (Mason, 1980;McGee, Lomax, & Head, 1988). Recent research results indicate that LNK may have a much more influential role in the first stages of literacy acquisition by promoting the emergence of a phonologically-based strategy in early spelling and reading.…”
Section: Letter-name Knowledge As a Bridge Towards Alphabetic Literacymentioning
confidence: 98%